Usability Evaluation of the Mendeley Website Using System Usability Scale (SUS) - Ni Luh Putu Lilis Sinta Setiawati; I Kadek Agus Hendriawan Putra; I Gusti Ngurah Bagus Hermaya Krisna; I Kadek Dony Suryadana (Study Program of Industrial Engineering, Udayana University, 2026)
A scientific paper is a writing that follows scientific principles and research ethics, supported by reference citations. Mendeley facilitates reference management; however, many students are not yet accustomed to using it. This study aims to evaluate the use of Mendeley and identify areas for improvement. The research method employed usability testing with the System Usability Scale (SUS) instrument. Statistical testing was also conducted, involving 24 students from the Industrial Engineering Program at Udayana University. Participants completed five task scenarios related to Mendeley features. Data on system effectiveness and efficiency were collected during the trials. The results show that Mendeley achieved an SUS score of 72.1, indicating an acceptable usability level with a Grade C and a “good” adjective rating. System effectiveness reached 100%, with all participants completing all tasks. Efficiency evaluation showed a rate of 0.177 goals/second, meaning users could complete 0.177 tasks per second. Statistical analysis indicated no significant differences in SUS scores or system efficiency based on gender. Furthermore, there was no correlation between SUS scores and system efficiency. These findings suggest that usability ratings are not directly related to system efficiency.